OBE Module for Placement of Undergraduate Program Students - Jayashree, V.; Kadage, A. D.; Patil, S. A.; Joshi, G. S. (Journal of Engineering Education Transformations, 2016)
The scenario of engineering education in India is changing through the National Board of Accreditation (NBA) process which has shifted its focus from output based education to Outcome Based Education (OBE). Purpose of monitoring the OBE is to manage the attainment of graduate attributes as required by many quality assurance guidelines. Maintaining right quality in education is essential for the overall growth of human race to sustain. Hence it can be said that, quality is not a choice but it should be mandatory. The purpose of this paper is to develop and test amodel for understanding application of levels of Bloom's taxonomy and hence to determine its impact on student's learning process. This paper discusses on the impact analysis of OBE module designed and implemented for improving the employability of the undergraduate students. Choice of test modules for OBE module was done as per the common placement criterions of companies by conducting the sessions such as technical test, aptitude test, and the personal interviews. The pre-test in all three categories helped us to analyze the grey areas of students and design training accordingly. The post test portrayed that, training based on results of pre-test could improve the performance of the students at apply and analysis level. Thus OBE based placement module has justified its importance in enhancing the ability level of students for quality placement.